Interplanetary shock data base - Oliveira, Denny (Frontiers, 2023)
Interplanetary (IP) shocks are frequently observed in the solar wind (Burlaga, 1971; Stone and Tsurutani, 1985). Many levels of different kinds of geomagnetic activity may follow the impact of IP shocks on the Earth’s magnetosphere. Such effects are seen everywhere in the magnetosphere-ionosphere system, including radiation belt dynamics, magnetic field in geosynchronous orbit, field-aligned currents, ionospheric disturbances, satellite orbital drag, ground magnetometers, geomagnetically induced currents (GICs), and others (e.g., Echer et al., 2005; Tsurutani et al., 2011; Khazanov, 2016; Oliveira and Ngwira, 2017; Oliveira and Zesta, 2019; Abda et al., 2020; Smith et al., 2020; Bhaskar et al., 2021). The study of IP shocks is important for space weather purposes because shock impacts occur more frequently than geomagnetic storms and correlate well with solar activity (Oh et al., 2007; Kilpua et al., 2015; Echer et al., 2023). Therefore, keeping an updated and accurate IP shock data base is of primary importance to the scientific community. Many IP shock parameters control shock geoeffectiveness, such as shock speeds, Mach numbers, and compression ratios (Craven et al., 1986; Kabin, 2001; Goncharov et al., 2014). Additionally, the shock impact angle, the angle the shock normal vector performs with the Sun-Earth line, has been shown to be a significant factor that controls shock geoeffectiveness (Oliveira and Samsonov, 2018; Oliveira, 2023). Many works have demonstrated with simulations and observations that, in general, the more frontal and the faster the shock, the higher the subsequent geomagnetic activity observed from the geospace to the ground (e.g., Takeuchi et al., 2002; Guo et al., 2005; Wang et al., 2006; Oliveira and Raeder, 2014; Oliveira and Raeder, 2015; Samsonov et al., 2015; Oliveira et al., 2016; Selvakumaran et al., 2017; Oliveira et al., 2018; Baker, 2019; Rudd et al., 2019; Shi et al., 2019; Oliveira et al., 2020; Xu et al., 2020; Oliveira et al., 2021). The main goal of this short report is to release an expanded version of an IP shock data base that was published before (Oliveira and Raeder, 2015; Oliveira et al., 2018). A major component of this new shock data base is a revision of the methodology used to calculate shock impact angles and speeds with respect to past versions of this list. Additionally, more shock and solar wind parameters before and after shock impacts and geomagnetic activity information were included in the list. This article is organized as follows. Section 2 discusses the methodology used for the computation of shock properties, including the data used and shock normal calculation methods. A shock example is shown in Section 3. Section 4 presents the IP shock data base and its components. Finally, Section 5 brings a few suggestions for future usage of this shock list, with focus on the role of shock impact angles in controlling the subsequent shock geoeffectiveness.